Propylene Carbonate in Organic Synthesis: Exploring its Potential as a Green Solvent - S. Bello Forero, Josué; A. Hernández Muñoz, July; Jones Junior, Joel; M. da Silva, Flavia (Current Organic Synthesis, 2016)
Propylene carbonate (PC) is a polar aprotic substance with very similar physicochemical characteristics to the organic solvents traditionally used for organic synthesis, such as acetonitrile and acetone. Therefore, PC is beginning to be used as a “green” sustainable alternative solvent for chemical transformations. PC is a low toxicity, non-corrosive colourless liquid with a high boiling point and low vapour pressure. It is biodegradable and economical, allowing its large-scale use. PC can be prepared by a reaction between propylene epoxide and carbon dioxide with 100% atomic economy. The easy preparation of propylene epoxide and the use of an available, abundant, economical, and renewable source of carbon, such as CO2, make this process one of the best routes for the synthesis of PC. Therefore, we present in this review numerous catalytic systems that have been studied to improve the efficiency of this reaction. Certain interesting examples of reactions using PC are found in the literature, of which we discuss asymmetric hydrogenation, hydrosilylation, asymmetric aldol reactions, the asymmetric synthesis of cyanohydrins, the synthesis of heterocyclic compounds, such as bisindole and tetrahydroquinoline, the hydroacylation of alkynes, α-hydrazination reactions, oxidations, the Sonogashira reaction, allylic alkylation and asymmetric amination, the Heck reaction, enzymatic kinetic resolution, and isomerisation-hydroformylation reactions.
Keywords: organic synthesis